LANGUAGE COMPETENCE OF STUDENT TOWARD RIGHT HEMISPHER BRAIN FUNCTION : A Neuropragmatic Study - Handoko Handoko; Gusdi Sastra; Ike Revita (Masyarakat Linguistik Indonesia Universitas Andalas, 2015)
It has been known that the right hemisphere is contributed to language processing, especially in macro level, including macrostructure or discourse processing. This research is aimed at evaluating the students' ability in language processing concerning macrostructure and the right hemispher brain function. This research is based on Dharmaperwira-prins method 'Right Hemisphere Communication Assessment' (Pemeriksaan Komunikasi Hemisfer Kanan/PKHK). Research on students' ability in macrostructure processing is important to conduct since students nowadays are regarded lack of ability in well being communication. The research is conducted toward 38 students of English Department of Andalas University. The data are taken by paper test which is designed to evaluate the students' ability in macrostructure. The result of research shows that most students have problems in providing important information, adjective, and feeling. By this result, it can be assumed that the participants have problem in right hemisphere competence concerning to language processing. These problems evoke not by accident or lesion in right hemisphere, yet it is caused by brain development which is focused on left hemisphere only. Keyword: Right Hemisphere, Language Assessment, Lexical Semantic, Macrostructure, Pragmatic